Інформаційний комплекс розподільних електромереж - Павленко, Я. С.; Булага, В. А. (ХНУРЕ, 2022)
The IR RES set is designed to monitor the main technical parameters of normal and emergency modes of 10 (6) kV distribution electrical networks (voltage, the appearance of an interphase short circuit current), as well as meteorological conditions (temperature and relative humidity) in the places of operation and data transmission to control room through the GSM networks of operating operators. The IR RES set is used to optimize the search and localization of the place of damage to overhead power lines with voltage 10(6) kV, as well as to prevent emergency conditions as a result of the influence of climatic factors.